INVENTORY INTENSITY CAN MODERATE THE EFFECT OF CAPITAL INTENSITY ON TAX AGGRESSIVENESS - Fadlilah, Andi Hidayatul; Marjono, Marjono; Tampubolon, Amy Septrina; Meidiana, Rebeka; Rahayu, Siti (JURNAL ILMIAH EDUNOMIKA, 2025)
ABSTRACTThis research is a quantitative study with an explanatory approach, namely an approach that relies on a number of previous studies as the main milestones to build and strengthen arguments in the hypotheses that researchers present slowly. The data used in this article are secondary data that researchers obtained from the Indonesia Stock Exchange from 2011 to 2021. The data obtained were analyzed using the smart PLS 4.0 analysis toolÂ  that the Capital Intensity variable does have a positive relationship direction and a significant influence on Tax Aggressiveness. This is because the P-Value tends to be positive and is below the significance level of 0.05, namely 0.000.. In addition, in the next hypothesis, it is also true that the Inventory Intensity variable can strengthen the influence of the Capital Intensity variable on Tax Aggressiveness. This is because something similar if the P-Values are positive and below the significance level of 0.05, namely 0.000, is smaller than the direct test of 0.008Â Keywords: Inventory Intensity, Capital Intensity, Tax AggressivenessÂ